Enhancement of in vivo hypoglycemic effect of gliclazide by developing self-microemulsifying pellet dosage form - Hetal Patel; Niharika Pandey; Bhoomi Patel; Ketan Ranch; Kunjan Bodiwala; Bhavin Vyas (SpringerOpen, 2020)
Abstract Background The present research was aimed to develop a self-microemulsifying drug delivery system (SMEDDS) pellet to increase the dissolution rate and in vivo hypoglycemic effect of gliclazide. Gliclazide belongs to BCS class 2 and it exhibits dissolution rate-limited absorption. Thus, dissolution enhancement of gliclazide from its dosage form is a prime requirement to achieve a better therapeutic effect. The solubility of gliclazide was estimated in oils, surfactants, and co-surfactants. A most effective self-emulsification region was identified using pseudoternary phase diagrams. The optimized liquid SMEDDS gliclazide formulation was converted to SMEDDS pellets using the extrusion-spheronization technique. The in vitro release and hypoglycemic effect of SMEDDS was compared with the marketed product. Results The optimized liquid gliclazide SMEDDS formulations contained mixtures of Tween 80 and PEG 400 and Capmul MCM C8. The gliclazide SMEDDS in liquid preparation quickly formed a fine oil-in-water microemulsion having a globule size of 31.50 nm. In vitro release of gliclazide from SMEDDS pellets was 100.9% within 20 min. SMEDDS pellets exhibited a significant reduction in plasma glucose levels in albino mice compared to the marketed product. Conclusion The results indicated that SMEDDS pellets could be effectively used to improve the oral delivery of gliclazide.